Combustion kinetics of lignite preheated under oxygen-enriched conditions. Issue 5 (August 2020) - Uğuz, Özlem; Haykiri-Açma, Hanzade; Yaman, Serdar
This study bases on the testing of the solid-state kinetic models to determine the combustion kinetics of thermally pretreated Turkish lignite (Adiyaman–Golbasi) in O2 -enriched environment. The lignite sample was first preheated in a horizontal tube furnace at temperatures of 200°C, 400°C and 600°C that correspond to torrefaction, partly devolatilization and partly ashing temperatures. Oxidative environments that have the O2 concentrations of 21, 30, 40 and 50 vol.%. were created during this treatment by changing the ratio of O2 /N2 in the binary gas mixtures. The solid residues remaining after oxidation were then subjected to non-isothermal combustion conditions in a thermal analyzer up to 900°C under dry air atmosphere. The conversion degrees calculated from the thermogravimetric analysis were used to establish the kinetic parameters based on the Coats–Redfern method. It was concluded that the first-order reaction model fits well for both the combustion of volatiles and the burning of the char. It was also seen that the concentration of O2 in the pre-oxidation stage plays an important role as treatment temperature also increases. Moreover, it was also concluded that the activation energies for the char burning regions of the samples treated at 200°C and 400°C differ seriously.